2017
DOI: 10.1111/bcpt.12705
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Carbon Nanotubes in Animal Models

Abstract: The many interesting physical and chemical properties of carbon nanotubes (CNT) make it one of the most commercially attractive materials in the era of nanotechnology. Here, we review the recent publications on in vivo biodistribution of pristine and functionalized forms of single-walled and multi-walled CNT. Pristine CNT remain in the lung for months or even years after pulmonary deposition. If cleared, the majority of CNT move to the gastrointestinal (GI) tract via the mucociliary escalator.However, there ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 64 publications
0
70
0
Order By: Relevance
“…The patter agrees with those reported for fullerenes and carbon nanotubes. For example, it was reported that long carbon nanotubes are mainly accumulated in lungs, Avti et al observed the same patter for gadonanotubes of 500 nm to 1.5 mm of length, by contrast. Also, it is well‐known small carbon nanotubes can be accumulated in bladder and kidneys, Marangon et al observed the functionalized gadonanotubes with average length of ≈400 nm, were mainly accumulated in bladder and kidneys.…”
Section: In Vitro and Animal Model Safety Assessmentsmentioning
confidence: 86%
See 2 more Smart Citations
“…The patter agrees with those reported for fullerenes and carbon nanotubes. For example, it was reported that long carbon nanotubes are mainly accumulated in lungs, Avti et al observed the same patter for gadonanotubes of 500 nm to 1.5 mm of length, by contrast. Also, it is well‐known small carbon nanotubes can be accumulated in bladder and kidneys, Marangon et al observed the functionalized gadonanotubes with average length of ≈400 nm, were mainly accumulated in bladder and kidneys.…”
Section: In Vitro and Animal Model Safety Assessmentsmentioning
confidence: 86%
“…This long‐term accumulation may represent a risk. A number of reports have found pristine CNTs remain in lungs for months or even years after pulmonary deposition, even more, the accumulation is associated with chronic inflammation and tissue damage . Particularly, the accumulation of MWCNTs in lungs is associated with fibrotic‐like lesions via non‐resolved chronic inflammation and the chronic exposure to SWCNTs may cause malignant transformation of human lung epithelial cells and induced tumorigenesis in mice .…”
Section: In Vitro and Animal Model Safety Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Saito and coworkers evaluated the pharmacokinetics of heavy metal-doped SWNTs in vivo using an advanced in situ MRI technique. [34] Saito and coworkers evaluated the pharmacokinetics of heavy metal-doped SWNTs in vivo using an advanced in situ MRI technique.…”
Section: Toxicity and Pharmacokinetics Of Swntsmentioning
confidence: 99%
“…In the same time ADH is the therapeutic target in blocking ethylene glycol metabolising pathway by using ethylic alcohol as a powerful competitor for binding to the enzyme as its affinity is 67 times higher for ethanol compared to ethylene glycol [4]. The metabolic products of ethylene glycol are: glycoaldehyde, glycolic acid, glyoxylic acid, oxalic acid and calcium oxalate.…”
mentioning
confidence: 99%